An inverse problem for an elliptic equation in a spherical domain. Issue 10 (3rd October 2022) - Lee, Doo-Sung
Abstract : This paper deals with the problem of determining a radially dependent coefficient a ( r ) in the equation Δ u − a ( r ) u = 0, in the unit sphere Ω from the Dirichlet–Neumann data pair { u, ∂ u ∂ ν } | ∂ Ω . We discuss the uniqueness of this determination.